ANTIBIOGRAM OF PATIENTS WITH DIABETIC FOOT AT DR. SOEBANDI REGIONAL HOSPITAL OF JEMBER, INDONESIA - Enny Suswati; Habib Mustofa; Bagus Hermansyah; Dini Agustina; Elly N Sakinah (Fakultas Kedokteran UPN Veteran Jakarta Kerja Sama KNPT, 2023)
Diabetic foot is a complication of diabetes mellitus that uses antibiotics to control the infection as the primary therapy. This study aimed to determine the type of bacteria and antimicrobial sensitivity patterns in diabetic foot. The samples were taken from the medical records of the patients with diabetic foot, who performed the swab culture and antimicrobial susceptibility testing in the inpatient and outpatient care in dr. Soebandi Regional Hospital. The samples used were the patients diagnosed with diabetic foot from January 1, 2014, to December 31, 2018. The data in this study were univariately analyzed. Forty-three pathogens were isolated from 40 patients with 12 ESBL isolates. The most common bacteria found were Gram-negative (90.7%), including Escherichia coli (33.33%), Klebsiella pneumoniae (12.82%) Pseudomonas aeruginosa (12.82%), Enterobacter cloacae (7.69%) and Proteus mirabilis (7.69%). Then, there were also 9.3% Gram-positive bacteria of all isolates, with Staphylococcus aureus as the most dominant species (50%). The antibiotic antimicrobial susceptibility testing also showed that Imipenem, amikacin, fosfomycin, cefoxitin, and netilmicin were the most sensitive antibiotics. The most common type of bacteria found was Escherichia coli, while the antibiotic still sensitive in most bacteria was imipenem.